Pengaruh Konsentrasi Kalsium Propionat Terhadap Kualitas Mikrobiologis Roti Tawar Talas Kimpul Selama Penyimpanan - Feranti, Anzella Natalia Fransisca; Putra, I Nengah Kencana; Puspawati, Ni Nyoman (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 14 No 1 (2025): Jurnal ITEPA, 2025)
White bread is a popular food in Indonesia, with consumption levels increasing each year. In efforts to diversify white bread options, many local ingredients can be used as flour substitutes, one of which is kimpul taro flour. Typically, white bread has a shelf life of 2-3 days. Calcium propionate is a common food additive used as a preservative in bread, though its application in kimpul taro white bread has not been extensively studied. This study aims to examine the effect of calcium propionate concentration on the microbiological quality of kimpul taro white bread during storage and to determine the optimal concentration of calcium propionate. A factorial randomized block design was used, with two factors: calcium propionate concentration (0 ppm, 1000 ppm, and 2000 ppm) and storage duration (0, 3, and 6 days). Data were analyzed with analysis of variance, and significant results were followed by the Duncan Multiple Range Test. The findings revealed that calcium propionate concentration significantly influenced (P<0.05) the moisture content and yeast and mold numbers during storage, though it did not significantly affect (P>0.05) total microbial counts. On the initial day (day 0), calcium propionate concentration had a significant effect (P<0.05) on bread texture but did not significantly influence (P>0.05) aroma or taste. The optimal addition of calcium propionate was found at a concentration of 1000 ppm, which provided a shelf life of 3 days. Calcium propionate effectively inhibited mold and yeast growth in kimpul taro white bread during storage without altering its sensory qualities. Keywords: Calcium propionate, cocoyam bread, microbiology quality, shelf life